Value-Based Management Approach in Improving Organizational Performance and Sustainability - Sujoko Sujoko (TechTalent & Business Review, 2026)
Changes in the organizational environment, characterized by accelerated technology, globalization, and demands for accountability, have prompted a management approach that transcends short-term financial orientation. Conventional management that ignores the value dimension has the potential to weaken the quality of strategic decision-making and threaten organizational sustainability. This study aims to analyze the implementation of values-based management and its implications for organizational performance and sustainability. A qualitative approach with a case study design was used to gain an in-depth understanding of the internalization of values ​​in managerial practices. Data were collected through in-depth interviews, observations, and document reviews, then analyzed thematically and iteratively. The results indicate that values-based management serves as a normative foundation that guides the behavior of leaders and employees, strengthens intrinsic motivation, and improves the quality of individual and collective performance. Organizational values ​​also contribute to strengthening social legitimacy, managing reputational risk, and adapting to environmental changes. The integration of values ​​into leadership and human resource systems has been shown to support organizational sustainability ethically and sustainably. These findings confirm that values-based management is a strategic paradigm that integrates performance and sustainability over the long term